The College of Education and Its Students - Until Death Do Us Part - Edgar L. Sagan (Educational Considerations, 1975)
The response at a large university to a recent fund request to 10,000 Education alumni was answered by only 150, and one person sent a cryptic message by pledging 12 cents. What's the real meaning behind that message?